INTEGRATED MARKETING COMMUNICATIONS IN AGRIBUSINESS OF UKRAINE - MAYOVETS, Y.; KUZYK, O. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the modern agribusiness activities, which can hardly be imagined without the use of various means of marketing communications. However, increasing attention to the effectiveness of marketing tools requires that the Ukrainian agro-industrial enterprises use the integrated marketing communications. Thanks to the rational combination of different means of communication, the synergy effect can be achieved, which is a consequence of rational combination of various means of marketing communications and the result of the sum of each individual component prevails. This effect helps to combat sound effect, interference, information overload and limitations of perception that nowadays affect every consumer, regardless of the market in which the company operates.At the same time, many agribusinesses in Ukraine (especially big ones) use physical stores, websites, mobile applications, call centres, advertising, PR or other channels simultaneously. At that, modern communication tools significantly simplify the process of interaction with the target audience and often do not require significant costs for the promotion policy.The study proves the need for the rational combination of individual tools of marketing communications with simultaneous integration of all components of the marketing mix. Only provided that all information about the company and its products available in the market is not contradictory, we can expect special attention of a modern client, their loyalty, long-term interaction and special conditions of work in the market.The attention is drawn to the feasibility of creating a scenario of the agricultural enterprise’s path to its buyer: it is necessary to clearly define the role and importance of each channel and means of marketing communications in this process. When developing the integrated marketing communications, the marketers of Ukrainian agribusiness should pay particular attention to omnichannel marketing. It is the practice of integrating multiple channels in order to create a comprehensive and consistent customer service. It is also advisable to refer to converged media. They provide a simultaneous combination of paid, owned and free media channels. This combination can help reach a larger audience of customers.
Keywords: marketing communications; agrarian business of Ukraine; integrated marketing communications; sound effect; interference; marketing mix; omnichannel marketing; converged media